Impact of a stepwise protocol for treating pain on pain intensity in nursing home patients with dementia: A cluster randomized trial - Sandvik, RK (Eur J Pain, 2014)
BACKGROUND: Pain is frequent and distressing in people with dementia, but no randomized controlled trials have evaluated the effect of analgesic treatment on pain intensity as a key outcome. METHODS: Three hundred fifty-two people with dementia and significant agitation from 60 nursing home units were included in this study. These units, representing 18 nursing homes in western Norway, were randomized to a stepwise protocol of treating pain (SPTP) or usual care. The SPTP group received acetaminophen, morphine, buprenorphine transdermal patch and pregabalin for 8 weeks, with a 4-week washout period. Medications were governed by the SPTP and each participant's existing prescriptions. We obtained pain intensity scores from 327 patients (intervention n = 164, control n = 163) at five time points assessed by the primary outcome measure, Mobilization-Observation-Behaviour-Intensity-Dementia-2 (MOBID-2) Pain Scale. The secondary outcome was activities of daily living (ADL). We used a linear intercept mixed model in a two-way repeated measures configuration to assess change over time and between groups. RESULTS: The SPTP conferred significant benefit in MOBID-2 scores compared with the control group [average treatment effect (ATE) −1.388; p < 0.001] at week 8, and MOBID-2 scores worsened during the washout period (ATE = −0.701; p = 0.022). Examining different analgesic treatments, benefit was conferred to patients receiving acetaminophen compared with the controls at week 2 (ATE = −0.663; p = 0.010), continuing to increase until week 8 (ATE = −1.297; p < 0.001). Although there were no overall improvements in ADL, an increase was seen in the group receiving acetaminophen (ATE = +1.0; p = 0.022). CONCLUSION: Pain medication significantly improved pain in the intervention group, with indications that acetaminophen also improved ADL function. WHAT'S ALREADY KNOWN ABOUT THIS TOPIC? Many people with dementia experience pain regularly, but are not able to communicate this to their carers or physicians due to the limited self-report capacity inherent in the symptomatology of dementia. Few studies have investigated the direct effect of pain treatment on pain intensity in patients suffering from dementia, with previous studies using proxy measures of behavioural symptoms. WHAT DOES THIS STUDY ADD? A stepwise protocol to treat pain in nursing home residents with moderate to severe dementia significantly reduced pain intensity. Pain treatment by acetaminophen improved activities of daily living. There is an urgent need for a standardized approach to assessment and treatment of pain for nursing home residents with dementia.